Molecular markers and phylogenetic analysis of UPMT27, a field isolate of the Malaysian fowl adenovirus associated with inclusion body hepatitis - Ahmed, Salisu; Abdul Razak, Mariatulqabtiah; Bejo, Mohd Hair; Omar, Abdul Rahman; Ideris, Aini; Mat Isa, Nurulfiza (Universiti Putra Malaysia Press, 2021)
Inclusion body hepatitis (IBH) is considered one of the re-emerging diseases of avian virus that causes economic damage worldwide. IBH is caused by different serotypes of fowl adenovirus (FAdV), and most of the FAdV cases in Malaysia are related to the serotype 8b. The objective of this study was to determine the molecular markers of UPMT27 Malaysian FAdV isolate and to identify the evolutionary relationship through the phylogenetic approach. Propagation of the isolate was made in embryonated chicken eggs and chicken embryo liver (CEL cells) before it was subjected to viral DNA extraction. Both the fiber and hexon genes of the isolate were amplified and sequenced. The sequences were aligned with the published FAdV sequences. The results showed 100% identity between UPMT27 and the previous Malaysian isolates. A phylogenetic study showed that UPMT27 was closely related to the previous Malaysian isolates. Interestingly, the substitution of the amino acids was consistent between the Malaysia isolates of both fiber protein at positions 72 (Serine –serine), 101 (Alanine -alanine), 125 (Glycine-glycine), and hexon protein 85 (Serine-serine) 160 (Glutamate- glutamate) and 205 (Alanine-alanine) respectively. It appeared that the amino acid variations were the indicators for genetic diversity. Thus, these findings provide information on the evolutionary relationship between FAdV subtypes for IBH prevention.